2014
DOI: 10.1007/s00246-014-1046-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Factors as a Predictor for Early Postoperative Outcomes After Repair of Congenital Transposition of the Great Arteries

Abstract: Transposition of the great arteries (TGA) requires early surgical repair during the neonatal period. Several preoperative factors have been identified for the postoperative poor outcome after arterial switch operation (ASO). However, the data remain uncertain an association. Therefore, we investigated the preoperative factors which affect the early postoperative outcomes. Between March 2005 and May 2012, a retrospective study was performed which included 126 infants with an ASO for TGA. Preoperative data inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
2
9
1
10
Order By: Relevance
“…In our study, simple TGA was found to be slightly more common than the complex forms, a finding which agrees with postnatal series [6,28] but that contrasts with previous prenatal studies reporting that the latter are more common [22]. These discrepancies may be attributed to the degree of distortion of cardiac anatomy that both types of TGA have, and hence, the ease of prenatal detection.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, simple TGA was found to be slightly more common than the complex forms, a finding which agrees with postnatal series [6,28] but that contrasts with previous prenatal studies reporting that the latter are more common [22]. These discrepancies may be attributed to the degree of distortion of cardiac anatomy that both types of TGA have, and hence, the ease of prenatal detection.…”
Section: Discussionsupporting
confidence: 76%
“…Patients received routine monitoring using 5-lead electrocardiography, pulse oximetry, noninvasive blood pressure, and capnography. In accordance with the standard protocol at our institution, [10,11] anesthesia was induced with midazolam (0.1–0.2 mg/kg), thiopental sodium (1.5–2.0 mg/kg), or ketamine (1–2 mg/kg), as appropriate. After the patient received vecuronium (0.15 mg/kg) and fentanyl (1–3 μg/kg), tracheal intubation was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Parameters assessed included baseline demographics and potential clinical risk factors for postoperative morbidity and mortality 5-9 (Supplemental Table 1). The Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery Congenital Heart Surgery STAT mortality categories 10 and operative times were abstracted from the institutional surgical database.…”
Section: Methodsmentioning
confidence: 99%